Profile Creative Dimenstion in The Strengthening Project of Pancasila Student Profiles in Elementary Schools - Wahyono, Wahyono (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2024)
The aim of this research is to analyze the Pancasila student profile strengthening project in the creative dimension of students in Kebumen elementary schools. Data collection techniques include documentation, interviews, and observations. The subjects of this study are students in IV. Data analysis employs the Miles and Huberman model, consisting of three stages: data reduction, data presentation, and data verification. The research results indicate that the creative of students in grades IV fall into the category of good. Teachers use various methods to develop creative dimensions such as using problem-based learning, cooperative learning, project-based learning, and contextual teaching and learning. The use of problem and project-based learning models is the most effective learning model in developing students' creative thinking abilities.